The Precambrian metallogeny of Kwazulu-Natal - Hira, Hethendra Gangaram (Rhodes University, Faculty of Science, Department of Geology, 1998)
The Precambrian rocks of KwaZulu-Natal comprise the Archaean granite-greenstone remnants of . the Kaapvaal craton and Late Archaean volcanics and sediments of the supracratonic Pongola Supergroup. These Archaean rocks have been intruded by numerous mafic/ultramafic complexes and voluminous granitoid intrusives of various ages. To the south, the basement rocks are represented by the Mid- to Late-Proterozoic Natal Metamorphic Province (NMP). The NMP comprises three discontinuity-bound tectonostratigraphic terranes. These are, from north to south, the Tugela, Mzumbe and Margate Terranes. The Tugela Terrane has been interpreted as an ophiolite suite that was thrust northwards onto the stable Archaean craton as four nappe structures. Continued thrusting resulted in the two southern terranes being thrust northwards over each other, resulting in numerous sinistral transcurrent shear zones and mylonite belts. The greenschist facies Tugela terrane has been intruded by mafic-ultramafic complexes, alpine serpentinites, plagiogranites and a number of alkaline to peralkaline granitoids. The Mzumbe and Margate Terranes comprise arc-related, felsic to mafic supracrustal gneisses and metasediments that were intruded by syn-, late- and post-tectonic granitoids. Mineralisation in the granite-greenstones consists of structurally-hosted lode-gold deposits. These deposits have many characteristics in common with lode-gold deposits found in other granitegreenstone terranes throughout the world. The Nondweni greenstones also contain volcanogenicrelated massive sulphide deposits. The Pongola Supergroup is host to lode-gold mineralisation and placer gold mineralisation. These placer deposits have been correlated with deposits found in the similarly-aged Witwatersrand Basin in an adjacent part of the craton. The metallogeny of the NMP can be described in relation to the various stages in the tectonic evolution of the belt. The initial, rifting and extension-related stage was characterised by arcrelated magmatism and volcanic arc activity. Alkali basalt magmatism due to hot-spot activity in the oceanic basin in which the Tugela Terrane initially accumulated, produced magmatic segregation deposits, while volcanic-arc activity is responsible for the submarine-exhalative massive sulphide mineralisation. All the mineralisation within the NMP is structurally-related. These thrusts and shear zones were developed during obduction and thrusting during the NMP event, and created the paths necessary for the migration of mineralising fluids. Alpine-type ophiolite deposits were also emplaced along these zones. Epigenetic, shear zone-hosted gold mineralisation occurs in the Tugela and Mzumbe Terranes. Mineralisation occurs within quartz veins and is also disseminated within the sheared host-rocks. The Mzumbe Terrane also contains small showings of massive sulphide deposits that were related to volcanogenic exhalative processes during the formation of this terrane. Potential for finding further mineralisation of this type appears to be good. The massive sulphide deposits formed early in the evolution of the belt, and were deformed and metamorphosed during the later accretionary processes. The southernmost Margate Terrane is characterised by a lack of metalliferous mineralisation, but hosts the extensive, and economically important, limestone deposits of the Marble Delta. The recently discovered spodumene-rich pegmatite deposits of this terrane may also be considered for exploitation. Post-collisional magmatism and metamorphism resulted in extensive rapakivi-type granite/charnockite plutons
Keywords: Metallogeny -- South Africa; Metallogeny -- South Africa -- KwaZulu-Natal; Geology, Stratigraphic -- Precambrian